Critical futures : community-engaged research in a time of social transformation - Poyntz, Stuart R.; Johal, Am; Grain, Kari, 1983- (University of Toronto Press, 2025)
"Critical Futures explores the evolving landscape of community-engaged research (CER) in a time of unprecedented social, political, and environmental crises. This collection brings together leading scholars, community researchers, and activists to examine the intersection of CER with social justice, decolonization, and transformation. The book explores the reimagining of CER and decolonizing research practices and offers case studies from the field. Through essays and contributions from a diverse group of scholars, the book highlights the need for ethical, equitable collaboration that transcends traditional academic hierarchies. It addresses topics including the role of solidarity in research, the impact of the COVID-19 pandemic on CER, Indigenous and Two-Spirit community research, and the critical importance of addressing power dynamics in university-community partnerships. With a focus on justice and the creation of new collective possibilities, Critical Futures provides both theoretical frameworks and practical examples that inspire a rethinking of how community research can contribute to a more just and sustainable future. This collection is essential reading for anyone interested in the future of research that is rooted in social change and community engagement."--